2018
DOI: 10.1021/acs.jafc.8b05673
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Hair, Oral Fluid, Earwax, and Nasal Mucus as Noninvasive Specimens to Determine Livestock Exposure to Teratogenic Lupine Species

Abstract: The livestock industry in the western United States loses an estimated $500 million annually from livestock production losses due to poisonous plants. Poisoning of livestock by plants often goes undiagnosed because there is a lack of appropriate or available specimens for analysis. The Lupinus species represent an important toxic plant in western North America that can be toxic and/or teratogenic to livestock species due to the quinolizidine alkaloids. The objective of this study was to evaluate the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These results concerning the detected chemical families are consistent with findings reported by other authors [ 20 ]. On the other hand, a recent study demonstrated a higher number of volatiles (42 compounds) in honey from China, which included 14 aldehydes, 12 ketones, seven alcohols, three acids, three pyrazines, one ether, one ester, and one terpene [ 34 ]. In Polish honey, we did not detect volatiles from ketone, pyrazine, ether, and terpene groups, but were identified compounds from groups of: Monoterpenes, disulfides, and furans, which were not detected in the Chinese samples.…”
Section: Resultsmentioning
confidence: 99%
“…These results concerning the detected chemical families are consistent with findings reported by other authors [ 20 ]. On the other hand, a recent study demonstrated a higher number of volatiles (42 compounds) in honey from China, which included 14 aldehydes, 12 ketones, seven alcohols, three acids, three pyrazines, one ether, one ester, and one terpene [ 34 ]. In Polish honey, we did not detect volatiles from ketone, pyrazine, ether, and terpene groups, but were identified compounds from groups of: Monoterpenes, disulfides, and furans, which were not detected in the Chinese samples.…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have measured fluoroacetate in earwax of cows that were experimentally administered sub-lethal doses of Palicourea marcgravii, a plant that causes sudden death syndrome in cattle, sheep, and goats in Brazil (4)(5)(6). Recently, earwax, hair, oral fluid, and nasal mucus were evaluated as noninvasive specimens to determine livestock exposure to poisonous larkspur plants and to toxic and teratogenic lupine plants (7). Lee et al (7) also demonstrated that lupine alkaloids could be detected in the earwax and hair of cattle over a 30-day period and that lupine alkaloids could be detected in the oral fluid and nasal mucus of cattle over an 8-day time after receiving a single oral dose of lupine plant material.…”
Section: Noninvasive Specimens For Plant Toxin/biomarker Analysismentioning
confidence: 99%
“…Recently, earwax, hair, oral fluid, and nasal mucus were evaluated as noninvasive specimens to determine livestock exposure to poisonous larkspur plants and to toxic and teratogenic lupine plants (7). Lee et al (7) also demonstrated that lupine alkaloids could be detected in the earwax and hair of cattle over a 30-day period and that lupine alkaloids could be detected in the oral fluid and nasal mucus of cattle over an 8-day time after receiving a single oral dose of lupine plant material. Lupine alkaloids were also detected in the earwax of cattle after a summer of grazing lupine-infested rangelands suggesting that plant alkaloids can persist in earwax months after exposure.…”
Section: Noninvasive Specimens For Plant Toxin/biomarker Analysismentioning
confidence: 99%
See 1 more Smart Citation